Relevansi Pacem In Terris dalam Konteks Globalisasi Modern (International Forum of Researchers and Lecturers, 2024)
Modern globalization has had a significant impact on interactions between countries, economies and cultures, but it has also created new challenges such as social injustice, intercultural conflicts and environmental crises. The encyclical “Pacem in terris” issued by Pope John XXIII in 1963 offers an excellent outlook to help address the complex challenges of modern globalization. This article aims to analyze the relevance of Pacem in Terris to address the problems of today's world and identify how the principles it promotes can be integrated into a complex global constellation. The method used in this research is qualitative analysis with literature review. The principles of “Pacem in Terris” such as respect for human rights, social responsibility and intercultural dialogue are essential to deal with today's world problems such as helping to overcome economic disparities, encouraging international cooperation, and strengthening collective consciousness to create peace.Modern Globalization, Paccem in teriis, Relevance